Modal analysis of cracked tower crane with an experimental validation - Trong, Dang Xuan; Toan, Le Khanh; Ngoc, Ha Thanh; Khiem, Nguyen Tien (Vietnam Journal of Science and Technology, 2020)
In this paper, dynamic stiffness model of a cracked frame structure that represents a planar tower crane is established in an explicit form based on general solution of cracked 2D-beam element vibration. The crack is modeled by a pair of equivalent springs of stiffness calculated from the crack depth. An explicit form of frequency equation is first established and then solved for numerical sensitivity analysis of natural frequencies of the structure to cracks. An experimental study is accomplished to validate the theoretical development